2009
DOI: 10.1111/j.1743-6109.2009.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sexual Orientation Using the Hemodynamic Brain Response to Visual Sexual Stimuli

Abstract: Introduction The assessment of sexual orientation is of importance to the diagnosis and treatment of sex offenders and paraphilic disorders. Phallometry is considered gold standard in objectifying sexual orientation, yet this measurement has been criticized because of its intrusiveness and limited reliability. Aim To evaluate whether the spatial response pattern to sexual stimuli as revealed by a change in blood oxygen level-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…In the first analysis including studies on male heterosexuals, we identified the importance of the hypothalamus, thalamus, left amygdala, ACC, left anterior insula, bilateral fusiform gyrus, left precentral gyrus, parietal cortex, and bilateral middle occipital cortex. Because there was considerably less data on sexual cue‐reactivity in women and homosexuals, we restricted our analysis to studies on male heterosexuals (for a study comparing homo‐ and heterosexuals, see [24]). A consistent relationship between brain activation and a physiological marker of sexual arousal was found in the hypothalamus extending into the thalamus, bilateral insula, ACC, left postcentral gyrus, and right middle occipital gyrus in a meta‐analysis on whole brain correlations with penile turgidity.…”
Section: Discussionmentioning
confidence: 99%
“…In the first analysis including studies on male heterosexuals, we identified the importance of the hypothalamus, thalamus, left amygdala, ACC, left anterior insula, bilateral fusiform gyrus, left precentral gyrus, parietal cortex, and bilateral middle occipital cortex. Because there was considerably less data on sexual cue‐reactivity in women and homosexuals, we restricted our analysis to studies on male heterosexuals (for a study comparing homo‐ and heterosexuals, see [24]). A consistent relationship between brain activation and a physiological marker of sexual arousal was found in the hypothalamus extending into the thalamus, bilateral insula, ACC, left postcentral gyrus, and right middle occipital gyrus in a meta‐analysis on whole brain correlations with penile turgidity.…”
Section: Discussionmentioning
confidence: 99%
“…This could be a valuable field for future research. Ponseti and colleagues [55], using specific sexual stimuli, even suggest that fMRI‐based classification methods could be used for the diagnosis of paraphilic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, heterosexual men showed activation in the bilateral lingual gyrus, right hippocampus, and right parahippocampal gyrus, areas that were not activated in homosexual men. Although Ponseti and colleagues [15] suggested that sexual orientation could be assessed by hemodynamic brain response to visual sexual stimuli, one study showed no difference in the pattern of activation between homosexual and heterosexual participants who were viewing faces of romantic partners of either the opposite or the same gender [16].…”
Section: Introductionmentioning
confidence: 99%